Transcanalicular multidiode laser versus external dacryocystorhinostomy in the treatment of acquired nasolacrimal duct obstruction - Bulut, Asker; Aslan, Mehmet Gökhan; Öner, Veysi (My University, 2021)
Objectives: This study was a comparison of the outcomes of transcanalicular multidiode laser dacryocystorhinostomy (TCLDCR) and external dacryocystorhinostomy (EXDCR) treatment for patients with acquired nasolacrimal duct obstruction. Methods: Thirty-one consecutive patients who underwent TCLDCR (TCLDCR group) and 68 consecutive patients who underwent EXDCR (EXDCR group) due to acquired nasolacrimal duct obstruction were enrolled in the study. Follow-up visits were performed on the first day, and at the first week, first month, third month, sixth month, and every six months thereafter. Surgical success was defined as achievement of a patent osteotomy and a successful bicanalicular silicone intubation during the procedure. Anatomical success was defined by observation of a patent osteotomy on lacrimal irrigation, regardless of epiphora. The surgery time and intra- and postoperative complications were noted for each patient. Results: The TCLDCR group had a significantly shorter mean surgery time (27.9±5.5 minutes) compared with the EXDCR group (58.5±12.0 minutes) (p<0.001). However, the mean anatomical and functional rates of TCLDCR (58.0% and 54.8%, respectively) were significantly lower than those of the EXDCR group (94.1% and 91.1%, respectively) (both p<0.001). Two patients had "cheese wiring" damage of the lower canaliculus and 1 patient in the TCLDCR group had a full-thickness skin defect in the medial canthal region. No serious intra- or postoperative complication occurred in the EXDCR group. Conclusion: Although a TCLDCR procedure decreased the surgical time, it had a significantly lower success rate in the treatment of acquired nasolacrimal duct obstruction compared to EXDCR. The decision of the type of surgery should be made based on the cosmetic and success expectations of the patients and the presence of systemic problems.
Keywords: Acquired Nasolacrimal Duct Obstruction; External Dacryocystorhinostomy; Transcanalicular Multdiode Laser Dacryocystorhinostomy